1986
DOI: 10.1073/pnas.83.23.9188
|View full text |Cite|
|
Sign up to set email alerts
|

Sequence homology between acquired immunodeficiency syndrome virus envelope protein and interleukin 2.

Abstract: [9188][9189][9190][9191][9192], the authors request that the following be noted. The last paragraph on p. 9188 should read: "Others have obtained experimental evidence indicating that the region of IL-2 that contains peptide IL2-A is important for activity. Ju et al. (25) used site-directed mutagenesis to determine that residues 21-40 of IL-2 (residues 1-20 of the mature protein) form one of the regions of IL-2 required for full biological activity and that this region is recognized by neutralizing anti-IL-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…This bias of human anti-HIV-1 towards recognition of peptides from the HIV-1 gpl20 and gp41 sequences probably cannot be ascribed to regions of homology between the virus glycoproteins and human host proteins. For example, peptide 808-845, sharing a region of homology with the human major histocompatibility complex class II peptide fl-domain (Golding et al, 1988) and peptides 411-445 and 38-61, sharing homology with the human immunoglobulin heavy chain constant region (Maddon et al, 1986) were not recognized by human anti-HIV-l. On the other hand, peptide 845-862 sharing homology with human interleukin 2 (Reiher et al, 1986) and peptide 61-90 sharing homology with the human immunoglobulin heavy chain constant region (Maddon et al, 1986) are recognized by human anti-HIV-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bias of human anti-HIV-1 towards recognition of peptides from the HIV-1 gpl20 and gp41 sequences probably cannot be ascribed to regions of homology between the virus glycoproteins and human host proteins. For example, peptide 808-845, sharing a region of homology with the human major histocompatibility complex class II peptide fl-domain (Golding et al, 1988) and peptides 411-445 and 38-61, sharing homology with the human immunoglobulin heavy chain constant region (Maddon et al, 1986) were not recognized by human anti-HIV-l. On the other hand, peptide 845-862 sharing homology with human interleukin 2 (Reiher et al, 1986) and peptide 61-90 sharing homology with the human immunoglobulin heavy chain constant region (Maddon et al, 1986) are recognized by human anti-HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Partial sequence homology between distinct segments of HIV-1 env glycoproteins and domains of functionally important host proteins suggested that immunization with the entire gpl20 + gp41 sequence may elicit harmful autoimmune responses (Maddon et al, 1986;Reiher et al, 1986;Golding et al, 1988;Brenneman et al, 1988). Selected regions from HIV-1 gpl20 and gp41 glycoproteins have immunosuppressive effects, suppress lymphocyte blastogenic responses and inhibit the activity of natural killer cells (Klasse et al, 1988;Nair et al, 1988;Cauda et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in addition to its direct cytopathic effects on human T helper cells, HIV-I, similar to other infectious agents (1, 2, 11), contains several epitopes which closely mimic self proteins (4, 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, similarities between HIV proteins and normal cellular proteins could elicit antiviral antibodies or cellular immune responses that crossreact with normal cells (74,868) (Table 31). Evidence in favor of this possibility includes the presence of IL-1, IL-2 receptor, MHC class I and class II, and interferon-like sequences in the HIV genes, as well as potential crossreacting epitopes on certain envelope portions of the virus (224,351,382,383,667,668,839,979). Moreover, crossreactive antibodies recognizing a platelet glycoprotein and an HIV gpl20 epitope have been cited as a possible mechanism for thrombocytopenia (70a).…”
Section: B Molecular Mimicrymentioning
confidence: 99%